The Iatriki Biblos (Book of Medicine) by Nikolaos Ieropais. Α 17th-century manuscript examined from a medical viewpoint - Leibaditou, Alexandra (DELTOS, 2024)
The “Iatriki Biblos” (“Book of Medicine”) is part of codex no. 46, hosted at the library of the Olympiotissa Monastery in Elassona, Greece. It is a medical manual that includes many diseases in the form of ailment groups, recording their aetiology, signs and symptoms on which diagnosis and the relevant therapy is based. This treatise constitutes a compendium of many Greek, Arab, Italian or French medical authors’ works. We have examined the “Biblos” from a medical viewpoint to find supporting evidence of: a. The scientific rigor of the text and its correlation with any possible theoretical basis regarding the signs and symptoms described. Although the classification system used today is different, it was possible to identify specific diseases based on the recorded signs and symptoms. Special attention was paid to the Greek terminology, because many terms are used to this day, with the same or different meanings. b. The influence of ancient medical authorities and the prevailing medical knowledge of Ieropais’ time. c. The usefulness or otherwise of the listed iamata (medicaments). We studied the active substances of the proposed plants, animal tissues and minerals, with the aim of ascertaining whether they had any positive or negative effect on the described symptoms. We discuss the problematic nature of such an investigation, as many essential details concerning their action as medicaments are absent. In conclusion, the 17th-century Greek doctor Nikolaos Ieropais adhered to the principles of natural philosophy in medicine of his time. His references to western Renaissance doctors of the 16th century add no new knowledge. The proposed therapies have a slight general and rarely a targeted effect.